Antibiotic Susceptibility, Virulence Pattern, and Typing of Staphylococcus aureus Strains Isolated From Variety of Infections in India - Aggarwal, Shifu; Jena, Smrutiti; Panda, Sasmita; Sharma, Savitri; Dhawan, Benu; Nath, Gopal; Singh, N. P.; Nayak, Kinshuk Chandra; Singh, Durg Vijai (Frontiers in Microbiology, 2019)
Staphylococcus aureus is one of the major causes of nosocomial infections. This organism produces powerful toxins and cause superficial lesions, systemic infections, and several toxaemic syndromes. A total of 109 S. aureus strains isolated from a variety of infections like ocular diseases, wound infection, and sputum were included in the study. MIC was determined against 14 antimicrobials. PCR determined the presence of 16S rRNA, nuc, mecA, czrC, qacA/B, pvl, and toxin genes in S. aureus isolates. PFGE, MLST, SCCmec, spa-, and agr-typing and serotyping determined the diversity among them. All isolates of S. aureus were resistant to two or more than two antibiotics and generated 32 resistance patterns. These isolates were positive for 16S rRNA and S. aureus-specific nuc gene, but showed variable results for mecA, czrC, and qacA/B and pvl genes. Of the 32 MRSA, 14 strains carried SCCmec type V, seven type IV, two type III and nine carried unreported type UT6. Of the 109 strains 98.2% were positive for hlg, 94.5% for hla, 86.2% for sei, 73.3% for efb, 70.6% for cna, 30.2% for sea and 12.8% for sec genes. Serotypes VII and VI were prevalent among S. aureus strains. PFGE analysis grouped the 109 strains into 77 clusters. MLST classified the strains into 33 sequence types (ST) and eight clonal complexes (CCs) of which 12 were singletons, and two belong to new allelic profiles. Isolates showed 48 spa-types that included two new spa-types designated as t14911 and t14912. MRSA and MSSA isolates were diverse in terms of antibiotic resistance pattern, toxin genotypes, SCCmec types, serotypes and PFGE, MLST, and spa-types. However, few isolates from eye infection and wound infection belong to CC239, ST239 and spa-type t037/t657. The study thus suggests that S. aureus strains are multidrug resistant, virulent, and diverse irrespective of sources and place of isolation. These findings necessitate the continuous surveillance of multidrug-resistant and virulent S. aureus and monitoring of the transmission of infection.